Characterization of Volatile Constituents from the Flowers and Leaves of Ailanthus altissima by Dynamic Head-Space Collection/GC-MS - Jiang1, Yifan; Ye2, Jiayan; Jiang3, Bao (Asian Journal of Chemistry, 2014)
Volatile chemicals emitted from the flowers and leaves of Ailanthus altissima were collected using a dynamic headspace technique and identified using gas chromatography-mass spectrometry. The total emission rates of volatile compounds from flowers (6086.18 ng/h/g) was about 11.4 folds as in the leaves (534.68 ng/h/g). Twenty-four fatty acid derivatives were identified from the flowers accounting for 16.09 % of the total emission rates of volatiles (979.18 ng/h/g), while ten fatty acid derivative compounds from the leaves accounting for 87.67 % of the total emission rates of volatiles (468.74 ng/h/g). The monoterpenoids linalool and (E)-geranial turned out to be the dominant compounds in the flowers accounting for 53.3 and 24.01 % of the total emission rate of volatile compounds repectively. Two Nitrogen-containing compounds were only present in the flowers of A. altissim.